CORRELATION OF PROTEINURIA AND GLUCOSURIA LEVELS IN TYPE 2 DIABETES MELLITUS IN KAMPUNG KLUMPANG, NORTH SUMATRA - Lee, Vanessa; Nasution, Sri Wahyuni; Fadillah, Qori (Universitas Negeri Gorontalo, 2024)
Diabetes mellitus is the sixth cause of death worldwide, with 90% of cases being type II diabetes mellitus (T2DM), which is characterized by decreased insulin response and increased insulin resistance. T2DM patients have a higher risk of complications and worse health outcomes due to Glucosuria and proteinuria. This study investigated the relationship between proteinuria and diabetes mellitus, which is a relatively new topic in the medical literature. Although there have been previous studies regarding diabetes complications, the role of proteinuria as an early indicator in T2DM patients has not been widely explored. This study aims to improve the understanding and management of this condition by assessing the relationship between levels of proteinuria and Glucosuria in T2DM patients. This research was conducted in August 2024 at the Klumpang Village Office, Hamparan Perak. This cross-sectional study involved patients with blood glucose levels 126 mg/dL, HbA1c 6.5%, and who gave informed consent. Patients who meet the criteria are asked to provide a urine sample for measurement of proteinuria and Glucosuria using a dipstick test. Results showed that the average age of patients was â‰¤60 years, with a higher prevalence among women (ratio 55:44). Glucosuria and proteinuria were not detected in some patients (ratio 25:30). Among those with Glucosuria, 33.3% showed ++ levels. In contrast, the highest incidence of proteinuria was detected at trace levels (44.4%). The conclusion is that the Spearman's Rho correlation test revealed a moderate and statistically significant positive relationship between blood glucose levels, HbA1c, Glucosuria, and proteinuria (p0.05). In conclusion, blood glucose and HbA1c levels are positively associated with proteinuria and Glucosuria in T2DM patients.